The Implementation of the Presumption of Innocence in Law Enforcement Coverage by the Mass Media - Sipayung, Ronald Fredy Christian; Danil, Elwi; Mulyadi, Mahmud; Yunara, Edi (Ultimate Journal of Legal Studies, 2023)
The application of the presumption of innocence in the press has long been a subject of attention and debate, both within the legal community and among journalists themselves. However, until now, the debate has not reached a consensus. Debates have started to arise regarding how the provisions in the Constitution (1945 Constitution) should be interpreted regarding applying the presumption of innocence in the press field. The debate continues to the level of analyzing how the legal regulations on the presumption of innocence should be applied in the field of press, and even the technical implementation in reporting. This paper utilizes normative legal research with a descriptive-analytical approach. Secondary data is sourced from legal regulations in the field of the press. Through qualitative analysis, the research yields the following results: Firstly, the presumption of innocence is incorporated into the Journalistic Code of Ethics with the hope that mass media, in their reporting, will not fall into the trap of "trial by the press," which involves reporting that tends to "judge" someone, violating the principles of a fair trial. Reporting that tends to express opinions on the guilt of a suspect not only violates the fundamental principles of the rule of law, namely judicial independence but also infringes upon an individual's human rights by diminishing their right to a legal defense.